Remote programming for subthalamic deep brain stimulation in Parkinson's disease - Chen, Si; Xu, Shu-jun; Li, Wei-guo; Chen, Teng; Li, Chao; Xu, Shuo; Yang, Ning; Liu, Yi-ming (Frontiers in Neurology, 2022)
Introduction: Deep brain stimulation (DBS) of the subthalamic nucleus (STN) is effective for the treatment of Parkinson’s disease (PD). Moreover, remote programming is widely used in Mainland China. This necessitates evaluating the ability of remote programming to achieve the ideal postoperative effect. Therefore, we aimed to retrospectively evaluate the effects of different programming modes on the effectiveness of STN-DBS 12 months postoperatively in patients with PD. Methods: Clinical data were collected retrospectively, before and 12 months after surgery, in 83 patients with PD. Based on the programming modes voluntarily selected by the patients during 12 months postoperatively, they were divided into three groups, namely remote programming alone, hospital programming alone, and hospital + remote programming. We compared the programming data and the effects of different programming methods on STN-DBS-related improvements 12 months postoperatively among these groups. Furthermore, we analyzed STN-DBS-related improvements at 12 months postoperatively in 76 patients. Results: The effectiveness of STN-DBS was not influenced by the three programming modes. The postoperative Movement Disorder Society Unified Parkinson’s Disease Rating Scale scores did not reveal statistically significant differences between the remote alone and hospital alone programming groups, except for motor examination. The postoperative decline in the levodopa equivalent daily dose was most apparent in the hospital programming alone group. The programming frequency of the hospital + remote programming group was considerably higher than that of the remaining groups. Seventy-six patients with PD displayed good STN-DBS surgical efficacy. Conclusion: Programming modes do not influence the short-term efficacy of STN-DBS, and remote programming can yield a satisfactory surgical effect.